Legal Reform Urgency: A Critical Analysis of Notary Officials Convicted More Than Once with Imprisonment Sentences Below Five Years - Furqani, Alvie Naufal; Istiqomah, Milda; Sjafi’i, Imam Rahmat (IJBLE Scientific Publications Community Inc., 2024)
A Notary in Indonesia is a public official appointed by the Minister of Law and Human Rights of the Republic of Indonesia. Its function is crucial in ensuring certainty, order, and legal protection in the realm of civil law. In carrying out their duties, a notary is obliged to maintain the integrity and dignity of their profession by avoiding violations stipulated in the Notary Office Law and Code of Ethics. Administrative sanctions can be imposed on a notary who violates the rules, such as written warnings, temporary suspension, honorable discharge, and dishonorable discharge. Finally, dishonorable discharge can be applied when a notary faces the threat of imprisonment for five years or more. However, if the threat of imprisonment is less than five years, the notary still has the opportunity to resume their profession after serving the sentence. The issue arises when the Notary Office Law does not provide clear provisions regarding the imposition of penalties if a notary faces a criminal threat of less than five years more than once. This situation creates a legal norm vacuum and ambiguity in the role of the Notary Supervisory Board in determining sanctions against notaries who commit such violations.